Contribution of nitrogen from chicken manure to broccoli crop (Brassica oleracea L.) - Torres Nava, Daniel; Sandoval Castro, Engelberto; Peña-Cabriales, Juan José; Vera-Núñez, José Antonio (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2017)
The nitrogen (N) contribution from chicken manure to broccoli crop (Brassica oleracea L.) was evaluate using the 15N isotopic technique. Six treatments combining chemical fertilizer (N-phosphonitrate) and organic fertilizer (N-chicken manure) at a total rate of 300 kg N ha-1 were established: 1) 0 + 300; 2) 100 + 200; 3) 150 + 150; 4) 200 + 100; 5) 300 kg N-phosphonitrate ha−1 + 0 kg N-chicken manure ha-1; and 6) an unfertilized N control. Five replicates per treatment were established under a statistical design of random blocks. The highest yield of broccoli (heads) corresponded to treatments 200 kg N-phosphonitrate ha-1 + 100 kg N-chicken manure ha-1 and 300 kg N-phosphonitrate ha-1 yielding 16 and 17 Mg ha-1, respectively. The highest value of total N-uptake (347 kg N ha-1) was observed in treatment corresponding to 150 kg N-phosphonitrate ha−1 + 150 kg N-chicken manure ha−1. The 15N data indicate low values of N-fertilizer uptake (3.2-4.1%) when manure was applied. The N-phosphonitrate alone treatment showed a higher value of N-fertilizer (28.7-48.0%) than treatment 200 kg N-phosphonitrate ha−1 + 100 kg N-chicken manure ha−1 (4.5-5.1%). The N uptake by plants from manure was 29.5% average. The combination of chemical and organic fertilizers resulted in a higher total N-uptake. The constant application of manure to soil under broccoli production in Puebla region resulted in a significant contribution of soil N to the broccoli crop.